2013
DOI: 10.1186/1129-2377-14-2
|View full text |Cite
|
Sign up to set email alerts
|

Headache and mechanical sensitization of human pericranial muscles after repeated intake of monosodium glutamate (MSG)

Abstract: BackgroundA single intake of monosodium glutamate (MSG) may cause headache and increased muscle sensitivity. We conducted a double-blinded, placebo-controlled, crossover study to examine the effect of repeated MSG intake on spontaneous pain, mechanical sensitivity of masticatory muscles, side effects, and blood pressure.MethodsFourteen healthy subjects participated in 5 daily sessions for one week of MSG intake (150 mg/kg) or placebo (24 mg/kg NaCl) (randomized, double-blinded). Spontaneous pain, pressure pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 36 publications
4
50
0
Order By: Relevance
“…The stimulation parameters (current intensity and duration) were chosen in accordance with the safety criteria, for preventing any side-effects caused by cortical excitability modulation (Nitsche et al, , 2008Poreisz, Boros, Antal, & Paulus, 2007), and were commonly used in previous experiments for exploring visual cortex functions (e.g., Antal et al, 2004;Spiegel, Byblow, Hess, & Thompson, 2013;Spiegel, Hansen, Byblow, & Thompson, 2012;Vigan o et al, 2013). The stimulation intensity and duration were at the upper ends of tDCS protocols in order to ensure, as much as possible, that effects of tDCS would not be offset by the effects of presenting the potent gratings themselves.…”
Section: Tdcs Stimulationmentioning
confidence: 99%
“…The stimulation parameters (current intensity and duration) were chosen in accordance with the safety criteria, for preventing any side-effects caused by cortical excitability modulation (Nitsche et al, , 2008Poreisz, Boros, Antal, & Paulus, 2007), and were commonly used in previous experiments for exploring visual cortex functions (e.g., Antal et al, 2004;Spiegel, Byblow, Hess, & Thompson, 2013;Spiegel, Hansen, Byblow, & Thompson, 2012;Vigan o et al, 2013). The stimulation intensity and duration were at the upper ends of tDCS protocols in order to ensure, as much as possible, that effects of tDCS would not be offset by the effects of presenting the potent gratings themselves.…”
Section: Tdcs Stimulationmentioning
confidence: 99%
“…Baad‐Hansen and colleagues found a decrease in the pressure pain threshold (PPT) in the left masseter muscle after a single dosage of liquid MSG at low dosages (eg, 75 mg/kg of body weight), but no difference was found in PPTs in the right masseter or either temporalis muscle . Shimada and colleagues gave MSG (150 mg/kg of body weight) dissolved in lemon soda daily for five consecutive days to 14 healthy adults and reported decreased mean PPTs in the masseter muscle as compared to baseline on days 2 and 3 of administration . No change in mean masseter PPTs was noted in the same group of participants when they received normal saline (24 mg per kg of body weight) added to lemon soda.…”
Section: Possible Mechanisms Of Dietary Triggersmentioning
confidence: 99%
“…50 Glutamate is the most ubiquitous excitatory neurotransmitter in the body, 51 and it has been demonstrated to play a critical role in headache pathophysiology in animal models and human studies. 21,22,46,[52][53][54][55][56][57] Previous studies have detected a dose-response relationship when MSG is administered at increasing levels. [23][24][25] One study suggested that the threshold for reactivity may be 2.5 g 23 and anecdotally reported that a highly seasoned restaurant meal could provide as much as 5 g of MSG.…”
Section: Discussionmentioning
confidence: 99%